A network of noise: designing with a decade of data to sonify JANET - Emsley, Iain; De Roure, David; Chamberlain, Alan (2017)
The existing sonification of networks mainly focuses on security. Our novel approach is framed by the ways in which network traffic changes over the national JANET network. Using a variety of sonification techniques, we examine the user context, how this sonification leads to system design considerations, and feeds back into the user experience.